Ash Clouds, Fields of Sand. Volcanic Activity in Costa Rica and Its Impact on the Agriculture Sector, 1950–2017 - Coto-Cedeño, Wainer Ignacio (2018)
This article explains, from a historical perspective, the eruptive activity of the volcanoes in Costa Rica and its impact on agriculture and livestock during the period 1950-2017.  Specifically, the research analyzes how the "showers of ash" and gases expelled by the massifs affected the livestock sector and the crops of cotton, maize, rice, potatoes, and coffee, among others. The study is based on bibliographic documentation and primary sources available at the National Library, the National Emergency Commission (CNE), the National Archives of Costa Rica (ANCR), the Ministry of Agriculture and Livestock (MAG), the National Seismological Network (RSN), and the Costa Rican Volcanological and Seismological Observatory (OVSICORI).